Farm size, food security, and welfare: Descriptive evidence from the Ethiopian highlands - Abay, Kibrewossen; Hirvonen, Kalle; Minten, Bart (International Food Policy Research Institute, 2017)
This paper studies associations between farm size, food security, and welfare. Given agricultural land constraints and the rapidly increasing rural population in Ethiopia, with 26 million more people being projected to be residing in rural Ethiopia in 2030 relative to 2016, this is a major concern for the country.